MANAGEMENT OF COLORECTAL ANASTOMOTIC LEAK: IS IT POSSIBLE TO SAVE ANASTOMOSIS? - F. Sh. Akhmetzyanov; V. I. Egorov; A. I. Valeev; V. A. Bukhalova (Сибирский онкологический журнал)
Nowadays, colorectal anastomotic leak is a threatening surgical complication, especially in low and ultralow rectal resections. Attempts to resolve this problem fultimately lead to the creation of permanent stoma. Preservation of rectal anastomosis is an important task, because in case of its leakage, more than 50 % of patients will have the need for permanent stoma. In this article the authors review various treatment options for anastomotic leakage. Methods of treating presacral sinuses that resulted from mesorectumectomy and techniques of their drainage, as well as the effectiveness of endoscopic methods with biologic glue were discussed. Methods that do not lead to anastomotic leak are more preferable in terms of improvement of quality of life of patients and further prognosis.